2010
DOI: 10.1007/s10640-009-9339-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Subjective Well-Being Data for Environmental Valuation

Abstract: This paper explores the potential of using subjective well-being (SWB) data to value environmental attributes. A theoretical framework compares this method, also known as the lifesatisfaction approach, with the standard hedonic pricing approach, identifying their similarities and differences. As a corollary, we show how SWB data can be used to test for the equilibrium condition implicit in the hedonic approach (i.e., equality of utility across locations). Results for Ireland show that the equilibrium condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
150
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 48 publications
2
150
2
1
Order By: Relevance
“…In fact, this introduces measurement error as satisfaction with life is a discrete variable, which is censored from above and from below. However, the bias resulting from this measurement error has been found to be minor in practice (see, for example, Ferrer-i-Carbonell and Frijters (2004) for panel data and Brereton et al (2008) and Ferreira and Moro (2010) for repeated cross-section data).…”
Section: Mitigating Endogenous Residential Sortingmentioning
confidence: 99%
“…In fact, this introduces measurement error as satisfaction with life is a discrete variable, which is censored from above and from below. However, the bias resulting from this measurement error has been found to be minor in practice (see, for example, Ferrer-i-Carbonell and Frijters (2004) for panel data and Brereton et al (2008) and Ferreira and Moro (2010) for repeated cross-section data).…”
Section: Mitigating Endogenous Residential Sortingmentioning
confidence: 99%
“…The effects of precipitation, wind speed, rainy days and hours of sunshine on SWB can be different based on the study area. For instance, wind has negative effect on SWB in Ireland (Moro et al, 2008;Ferreira and Moro, 2010). Welsch (2002; found a negative relationship between SWB and air pollution factors at country level.…”
Section: Resultsmentioning
confidence: 96%
“…Diener et al (2009) and Moro et al (2008) found that people (based on the subjective well-being) who are living proximity to the coastline are happier. Ferreira & Moro (2010) mentioned that coastline is not significant factor for happiness if the distance is more than 5 km.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations